(untitled) (Педагогіка вищої та середньої школи, 2006)
Grading is a basic method of the credit-modulus system. The increasing interest of students in the ultimate result completes more conscious and active attitude toward educational activity. The article deals with the principal methodical recommendations on the construction and of delivering the course.